Last Mile Delivery Box Packing - Mizusawa, Yuri Masakazu (2023)
The growth of e-commerce is leading to a significant increase in parcel shipments, making it essential to optimize the packaging process. This study investigates packaging models that aim to minimize the amount of empty space during transportation. First, packing models are solved with exact methods to analyze their efficiency and speed, highlighting the effectiveness of item rotation and alternative formulations. Two scenarios are explored: comparing box sets generated in this work with sets from the literature, and allowing items from the same customer to be packed in two boxes. Both scenarios show a significant reduction in residual volume. In the second part of the work, a local search method is developed to adjust the dimensions of the boxes. This method is effective in reducing empty space and has practical implications for logistics optimization in the context of e-commerce.